Poor immune response to inactivated COVID-19 vaccine in patients with hypertension - Yang, Lei; Zeng, TingTing; Li, Yang; Guo, Qiao; Jiang, DePeng (Frontiers in Medicine, 2024)
Purpose The safety and efficacy of vaccination in people with hypertension (HTN) is important. There are currently a few data on the immunogenicity and safety of inactivated SARS-CoV-2 vaccinations in hypertension patients. Methods After receiving a two-dose immunization, 94 hypertension adult patients and 74 healthy controls (HCs) in this study, the evaluation included looking at antibodies (Abs) against receptor binding domain (RBD) IgG, SARS-CoV-2 neutralizing antibodies (NAbs), RBD-specific B cells, and memory B cells (MBCs). Results There was no discernible difference in the overall adverse events (AEs) over the course of 7 or 30 days between HTN patients and HCs. HTN patients had lower frequencies of RBD-specific memory B cells and the seropositivity rates and titers of Abs compared with HCs (all, p < 0.05). HTN patients with cardiovascular and cerebrovascular conditions (CCVD) have lower titers of CoV-2 NAb than in HCs. The titers of both Abs in HTN declined gradually over time. Conclusion Inactivated COVID-19 vaccinations were safe in hypertension patients; however humoral immune was limited, especially merged CCVD and declined gradually over time.